Essays on interest rates - Guttentag, Jack M.; Cagan, Phillip (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1971)
The essays in this volume , which further extend the National Bureau's work on interest rates fall broadly into three groups. These are concerned with patterns of interest rate fluctuations on a wide variety of instruments; selected determinants of yield on risk instruments; and determinants of maturity structure on riskless securities.
Vol. 2 edited by J. M. Guttentag.
Includes bibliographical references.
oif 04/02/2019
Loans
Keywords: Interest rates